2015
DOI: 10.1111/tmi.12602
|View full text |Cite|
|
Sign up to set email alerts
|

Use of antibiotics by urban and rural residents in Heilongjiang Province, China: cross‐sectional study

Abstract: Abstractobjective To identify and compare the factors affecting the knowledge of, attitude towards and use of antibiotics between urban and rural residents in China.methods A total of 3631 urban and rural residents in Heilongjiang Province, China, were selected using random sampling. Questionnaires recorded demographic characteristics and participant knowledge of, attitude towards and use of antibiotics. The responses of rural and urban residents were compared, and logistic regression analysis was applied to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 16 publications
4
18
1
Order By: Relevance
“…This finding underscores the challenge of changing human behavior and suggests the need for new approaches to promote better stewardship of antibiotics at the community level. Similar to previous studies [11,31,32], women in our sample had higher knowledge compared to men. Of particular concern was the high proportion of younger individuals who had used antibiotics in the year preceding the survey, given the lower level of knowledge observed in this group.…”
Section: Knowledgesupporting
confidence: 90%
See 1 more Smart Citation
“…This finding underscores the challenge of changing human behavior and suggests the need for new approaches to promote better stewardship of antibiotics at the community level. Similar to previous studies [11,31,32], women in our sample had higher knowledge compared to men. Of particular concern was the high proportion of younger individuals who had used antibiotics in the year preceding the survey, given the lower level of knowledge observed in this group.…”
Section: Knowledgesupporting
confidence: 90%
“…We selected four main independent variables to include in our analysis; place of residence/region (Greater Accra, Upper West), gender (female, male), education (primary or lower, junior high school, senior high/vocational school, tertiary (university degree or currently enrolled)), and age (18-24; 25-34; 35-44; 45-54; 55-64; 65+). This was based on similar KAP studies which found significance for these variables [11,14,31].…”
Section: Independent Variablesmentioning
confidence: 98%
“…The majority of the studies (20 studies) were conducted as single-country studies while 2 studies were multi-country studies at global and regional levels [1,4]. Among the 20 singlecountry studies, 8 studies were conducted at national level [6,12,13,14,15,16,17,18] while the remaining 12 studies were conducted at sub-national level [11,19,20,21,22,23,24,25,26,27,28,29]. It should be noted that no study was conducted in the African region.…”
Section: Characteristic Of 22 Studiesmentioning
confidence: 99%
“…For sampling criteria, nearly half of studies (10 out of 22) recruited only adults over 15, 18 or 21 years old [1,4,6,13,14,17,18,21,22,25]. Some studies [11,12,15,16,24,26,27,28,29] had additional criteria such as respondents' understanding of local languages, familiarity with the term "antibiotics" or whether they had lived in households or the geographical area for a certain period.…”
Section: Characteristic Of 22 Studiesmentioning
confidence: 99%
See 1 more Smart Citation